Prosodic Noun Incorporation: The Relationship between Prosody and Argument Structure in Niuean. (28th March 2019) - Clemens, Lauren
Abstract: This paper argues for a uniform X 0 ‐raising analysis of VSO and VOS word order in Niuean. Accounting for VSO via X 0 raising has a strong foundation in the V1 literature; the claim that X 0 raising can also underlie VOS word order—as in Niuean's pseudo‐noun‐incorporation construction—is more controversial. This paper explains the VOS order of Niuean pseudo noun incorporation by appealing to a condition on prosodic well‐formedness, Argument ‐ φ, that requires a head and its internal argument(s) to form a unique phonological phrase. In order to satisfy this requirement, the incorporated argument undergoes prosodic restructuring into a position adjacent to the verb at PF. Since the verb arrives at its clause‐initial position via X 0 raising, the syntactic input to the prosodic grammar is VSO, while the prosodic output is VOS.